A Case Study ASUHAN KEPERAWATAN PADA NY. B DENGAN SKIZOFRENIA MELALUI TERAPI AKTIVITAS TERJADWAL RUMAH SAKIT JIWA - Wulida Litaqia (Indonesian Journal of Nursing Scientific, 2024)
Background: Mental health problems have become an unresolved health problem in society, both globally and nationally. Hallucinations are a condition in which a client experiences changes in sensory perception caused by stimuli that are not actually there. The application of scheduled activities to clients with hallucinations is quite efficient in helping to control the onset of hallucinations by reducing the client's free time filled with various activities. Objective: The purpose of this study was to analyze the application of scheduled activity therapy nursing actions to reduce the level of hallucinations of Schizophrenia clients in the K ward of the West Kalimantan Provincial Mental Hospital. Method: The method in this scientific paper is focused on a descriptive case study of clients with hallucination disorders, with a focus on the study of the application of scheduled activities. Data collection using interviews, physical examinations, observations and presented in the form of descriptive case analysis reports. Results: The results obtained from this study were that clients who received scheduled activity therapy experienced a decrease in the level of hallucinations. Conclusion: The conclusion of this study is that the application of scheduled activity therapy has proven effective in reducing the symptoms of hallucinations experienced by Schizophrenia clients in the K ward of the West Kalimantan Provincial Mental Hospital